(untitled) (Current Problems in Rail Vehicles, 2021)
One of the most important parameters, which are measured on the rail, is the coefficient of adhesion (CoA). CoA on real rail is measured by measuring locomotive or measuring carriage. These methods are quite expensive, therefore rail tribometers which are fixed or pushed are used. Developed track tribometer is mounted on a rail above the measured section. The main part of the device is a measuring module, which is dragged by a stepper along a linear guide mounted on the frame. CoA is obtained by controlling the change in traction force, which is realized by breaking the measuring wheel. During the measurement, the braking torque, forward and rotational speed are recorded. Based on these data, it is possible to plot the adhesion curve in the measured section. The paper discusses the various measuring modes of the tribometer and presents the methodology of adhesion measurement. Moreover, a series of measurements in the presence of various contaminants was performed in a laboratory.